Normative Database of Optical Coherence Tomography Parameters in Childhood - Queirós, T (2015)
INTRODUCTION: Optical coherence tomography is a technology that allows obtaining high resolution images of tissues in vivo, enabling the measurement of ocular structures, including the retinal nerve fiber layer and macular thickness. As a noninvasive test itâÄôs particularly useful in children, but its applicability is limited by the existence of normative values for adults only. PURPOSE: To establish the pediatric normative values of retinal nerve fiber layer thickness and macular thickness and to investigate its relationship with sex, age, refraction, eye side and ocular dominance. MATERIAL AND METHODS: Ophthalmologic examination and Cirrus HD-optical coherence tomography (Carl Zeiss Meditec) were carried out on 153 children aged 4 to 17 years old. RESULTS: We obtained a mean retinal nerve fiber layer average thickness of 97.90 Î¼m. No significant differences were detected between genders, however the eye side and ocular dominance had significant influence on retinal nerve fiber layer thickness. Retinal nerve fiber layer thickness increased significantly with more positive refraction. With the Macular Cube 512 x 128 protocol we found that the average central subfield showed the smallest thickness (250.35 Î¼m) and boys had higher macular thickness. DISCUSSION: The values of the retinal nerve fiber layer thickness and macular thickness obtained are comparable to recent studies. The distribution of retinal nerve fiber layer thickness in quadrants is in agreement with the normal distribution of retinal nerve fiber layer. Macular thickness proved to be higher in males (center field and inner ring), data consistent with previous studies. CONCLUSION: We establish the normative retinal nerve fiber layer thickness and macular thickness in healthy Portuguese children. These data enhance the evaluation and interpretation of parameters obtained by optical coherence tomography in the diagnosis of pediatric disorders in clinical practice.